I. Compiled Stratigraphic Data from Cores Drilled at Mizuho Station (Appendix : Miscellaneous Compiled Data) - NARITA, Hideki; WATANABE, Okitsugu; SATOW, Kazuhide; OKUHIRA, Fumio (1978)
P(論文) departmental bulletin paper